Archaeological and Natural Indicators of Sea-Level and Coastal Changes: The Case Study of the Caesarea Roman Harbor - Ehud Galili; Amos Salamon; Gil Gambash; Dov Zviely (Geosciences, 2021)
Archaeological and geomorphological features, as well as traces left by tsunamis, earthquakes, and vertical earth-crust displacements, are used to identify sea-level and coastal changes. Such features may be displaced, submerged or eroded by natural processes and human activities. Thus, identifying ancient sea levels and coastal changes associated with such processes may be controversial and often leads to misinterpretations. We exemplify the use of sediment deposits and sea-level and coastline indicators by discussing the enigmatic demise of the Roman harbor of Caesarea, one of the greatest marine constructions built in antiquity, which is still debated and not fully understood. It was suggested that the harbor destruction was mainly the result of either tectonic subsidence associated with a local, active fault line, or as a result of an earthquake/tsunami that struck the harbor. Here we examine and reassess the deterioration of the harbor in light of historical records, and geological, geomorphological and archaeological studies of natural and man-made features associated with the harbor. We show that the alleged evidence of an earthquakes or tsunami-driven damage to the outer breakwaters is equivocal. There is no supporting evidence for the assumed tectonic, active fault, nor is there a reliable historic account of such a catastrophic destruction. It is suggested that geo-technic failure of the breakwater’s foundations caused by a series of annual winter storms was the main reason for the destruction and ultimate collapse of the western basin of the harbor. The breakwaters were constructed on unconsolidated sand that was later washed away by storm waves and sea currents that frequently hit the Israeli coast and undercut the breakwaters. The pounding effect of the waves could have contributed to the destruction by scouring and liquefying the sandy seabed underlying the foundations. Tsunamis that may have hit Caesarea could have added to the deterioration of the breakwaters, but did not constitute the main cause of its destruction.